Silent Crisis: Water Sanitation And Food Hygiene As Determinants of Stunting: (A Case-Control Study In Banjar Regency, Indonesia) - Deani, Ani Kipatul Hidayah; Khairiyati, Laily; Marlinae, Lenie; Husaini, Husaini; Arifin, Syamsul; Waskito, Agung; Rasyid Ridha, Muhammad; Nur Rahmat, Anugrah; Kamila Saleha, Anis (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2026)
Data from the Indonesian Nutrition Status Survey (SSGI) show that the prevalence of stunting in Banjar Regency increased from 17.68% (2021) to 26.4% (2022), and further rose to 30.6% (2023). Limited access to safe drinking water and food increases the risk of stunting through infectious diseases that disrupt nutrient absorption. This study aimed to analyze the relationship between water quality, food hygiene, and stunting among children under five in Banjar Regency. This research used case control study design. The case and control groups each received 30 samples. Independent variables included the source and quality of clean water (physical, chemical, microbiological), the source and quality of drinking water, drinking water management, and food hygiene practices (processing, serving, storage). Data were collected through household water sampling tested for physical (turbidity), chemical (pH, Fe), and microbiological (E. coli) parameters, as well as questionnaires and structured interviews with parents or caregivers. Data analysis was conducted using binary and multivariate logistic regression tests. The results showed that clean water sources, drinking water sources, microbiological quality of drinking water, drinking water management, and food management were significantly associated with stunting (p < 0.05). Multivariate analysis identified drinking water sources and food management as the primary determinants, jointly accounting for 18.4% of stunting occurrence. These findings underscore that stunting prevention interventions should be prioritized toward improving the safety of household drinking water and strengthening food hygiene practices.